Laser driver (ACC - auto current control) for driving laser diode in LED and laser modes - Tay, Eng Boon. (2008)
Arrive at an auto current circuit that can be used for driving a laser diode operating both in laser mode and LED mode. The circuit implemented is such that is portable and able to cater for few applications such as visual inspection of a laser diode and fiber checker.